Obesity and COVID‐19: A jigsaw puzzle with still missing pieces - Michalakis, Konstantinos (Clin Obes, 2020)
Apart from posing various mechanical and medical issues compromising general health, obesity is a major factor for respiratory tract infections, due to specific inflammation and immunological compromise. The burden of obesity on morbidity and mortality of SARS‐CoV‐2 infection/COVID‐19 is considerable. Herein, we aimed to search the literature and present to the readers pathophysiologic pathways that may associate obesity and COVID‐19. We present potential mechanisms, which might partly explain why patients with obesity are more prone to suffer from respiratory infections in the context of COVID‐19. Better understanding of these pathways could eventually guide management strategies and therapies for COVID‐19 in the future.